Innovative Technologies to Increase Bioactive Compounds in Carrots of the Chantenay Variety - Gutiérrez, Diego Ricardo; Ruiz, Silvana Cecilia; Benites, Julio Federico; Rodriguez, Silvia del Carmen (MDPI, 2025)
Artículo presentado al 5th International Electronic Conference on Foods, 28–30 October 2024